Environmental audit scoring evaluation: evolution of an evidence-based environmental assessment tool to support person-centered care - Wrublowsky, Robert A.; Kaup, Migette L.; Calkins, Margaret P. (Frontiers in Dementia, 2024)
Long-term care settings are at the center of strongly debated approaches to policies that shape the delivery of care and operational practices. There is advocacy for transformational change within these settings to support a person-centered approach to care delivery, but it is difficult and multifaceted involving everything from changing the level of staffing and care models to developing appropriate metrics to assess an individual's quality of life. The physical environment is a key component for accomplishing the organizational and operational goals related to personcentered care, but providers and their design teams need the appropriate tools to guide evidencebased decision-making. The Environmental Audit Scoring Evaluation (EASE) is a tool that helps lend structure to the process of developing the environment for our senior population-especially those living with dementia. This perspective article will discuss how EASE aims to align the design process to more fully support the myriad environmental elements that have a demonstrable impact on the individual, and the associated quality of life they experience. The article will also explore how EASE differs from previous planning strategies that did not prioritize residents' psychological well-being in conforming to current person-centered philosophies.